Legitimasi Pengaturan PPN Atas Lpg 3 Kilogram dalam PMK Nomor 62/Pmk.03/2022: Antara Delegasi Kewenangan, Distorsi Subsidi, dan Jaminan Kepastian Hukum - Mulyadi M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the conformity of the Value Added Tax (VAT) regulation on certain Liquefied Petroleum Gas (LPG), particularly 3-kilogram LPG cylinders, as stipulated in the Minister of Finance Regulation Number 62/PMK.03/2022. The issue is examined not merely as a conflict between a ministerial regulation and higher-ranking legal norms, but rather as a matter concerning the limits of delegated regulatory authority, the coherence between fiscal and subsidy policies, and the protection of legal certainty for business actors and consumers. This research employs a normative legal research method using both statutory and conceptual approaches. The findings indicate that the status of 3-kilogram LPG cylinders as an essential commodity under trade and energy policies does not automatically qualify them for specific VAT facilities. Minister of Finance Regulation Number 62/PMK.03/2022 formally derives its legal basis from Article 16G of the VAT Law and distinguishes the imposition of VAT on the portion of the price subsidized by the government from the portion that is not subsidized. Accordingly, any judicial review of the regulation should focus on the appropriateness of the scope of delegated authority, the clarity of the calculation formula, and the transparency of price allocation, rather than on the assumption that every subsidized commodity is automatically exempt from VAT